PENANGANAN PERILAKU MEMBOLOS SISWA DI MADRASAH TSANAWIYAH AL-IHSAN, SIDOARJO - Triana Rosalina Noor; Cholil (Conseils : Jurnal Bimbingan dan Konseling Islam, 2024)
The phenomenon of truant behavior in students is a real phenomenon experienced by schools. Responding to this requires handling from the school through the counseling teacher to follow up on student truant behavior. This research uses a qualitative approach as case study in MTs. Al-Ihsan Sidoarjo. The informants of this study were school principals and counseling guidance teachers, by using interviews, observation and documentation as data collection method which were then analyzed qualitative-descriptively. The findings showed that the handling of truant behavior that occurred in MTs. Al-Ihsan Sidoarjo was responded by counseling teacher in preventive and curative approaches. For the preventive approach, the counseling teacher provides advice and motivation to all students not to commit truant behavior. Apart from that, parenting sessions were also held as an educational effort and to establish communication with parents and to strengthen social control efforts by involving the role of the surrounding. In the curative approach, the counseling teacher conducts individual counseling sessions to students who have problems intensively to be able to explore reasons and determine solutions centered on the students' own awareness. In addition, the counseling teacher also conducts home visits to the house as a form of communication and checks the condition of students in the home environment. The last treatment taken by the school if truancy behavior is still being carried out is by enforcing discipline through imposing sanctions on students.